STUDI TERHADAP FATWA MAJELIS ULAMA INDONESIA BIDANG SOSIAL KEMASYARAKATAN DAN IPTEK - La Jamaa; Anwar Fahri (TAHKIM, 2021)
The existence of the Indonesian Ulema Council is very strategic in responding to the various dynamics of the development of Islamic law in Indonesia which are caused by the development of advances in science and technology. In this regard, MUI responded by issuing a fatwa. The MUI fatwa in the field of social affairs and science and technology uses maslahah al-ummat by setting aside the zahir verse that allows marriage between Muslim men and women who are ahlul Kitab. In the MUI fatwa, three approaches are used, namely the bayani approach with the al-nas signaling analysis system, and amar and nahy; istidlal analysis method, and istislahi analysis approach with fathu al-zari'at on the ability to implement family planning, as well as sadd al-zari'at, against the prohibition of using abortion and sterilization as family planning contraceptives as well as textual hadith and ratio considerations in the halal fatwa slaughter animals mechanically. Keywords: fatwa method, MUI, contemporary Islamic law